Preparation method of composite pole piece
Through the online component analysis and equipment parameter adjustment when metal lithium is coated on the electrode sheet or foil, the problem of difficult to accurately control the lithium foil content is solved, and the battery performance is significantly improved.
Patent Information
- Application Number
- CN202411539932.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
AI Technical Summary
During the process of overlying metal lithium with electrode sheets or foils, it is impossible to accurately judge the content of lithium foil during the preparation process, resulting in unstable battery cell performance.
By performing real-time component analysis during the process of covering metal lithium on the electrode sheet or foil, use laser-induced breakdown spectrometer or X-ray fluorescence spectrometer to determine the metal lithium content, and adjust the equipment parameters according to the analysis results to ensure that the lithium content is in the pre-premature Set within the scope.
The precise control of the lithium metal content on the electrode sheet or foil is achieved, the battery circulation and storage performance are improved, and the first-effect and cycling performance of the battery cell are significantly improved.
Smart Images

Figure CN119400809A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of communication equipment, and more specifically, to a method for preparing a composite pole piece. Background Art
[0002] In recent years, the rapid development of portable electronic products, new energy vehicles, smart grids, distributed energy storage, and the Internet of Things has continuously put forward higher requirements for the various performances of lithium-ion batteries, among which the improvement of battery cycle performance and energy density is the most urgent. During the formation process of lithium-ion batteries, lithium ions generate SEI films on the surface of the negative electrode, consuming active lithium, resulting in battery capacity loss. By introducing lithium ions in advance, active lithium can be compensated to achieve the effect of improving the energy density of lithium-ion batteries. The irreversible capacity loss of the most widely used graphite negative electrode is greater than 6%, while for silicon-based negative electrodes with high gram capacity, the irreversible capacity loss is even as high as 10% to 20%. Introducing lithium ions in advance for lithium supplementation can improve the shortcomings of low first efficiency, give full play to its high capacity advantages, further improve battery cycle performance and energy density, and greatly promote the development of lithium-ion batteries. At the same time, another form of lithium-ion battery-solid-state battery has gradually attracted attention due to its excellent energy density and safety performance, but there are still some technical difficulties to be overcome in the metal lithium negative electrode of solid-state batteries, such as the preparation of copper-lithium composite belts; Since metallic lithium has a high capacity and will not introduce other substances, it is the most ideal material for replenishing lithium ions, including metallic lithium powder, metallic lithium foil, metallic lithium bars, metallic lithium blocks, etc. Some researchers add pure lithium powder or lithium powder coated with lithium carbonate to the negative electrode slurry and stir, but this is incompatible with the aqueous solvent in the current negative electrode slurry making process and poses a safety hazard. There are also studies that coat a layer of metallic lithium foil on the negative electrode sheet by evaporation or calendaring, but the thickness of the lithium foil is difficult to control, which can easily lead to excessive or insufficient lithium when coating the lithium foil or evaporating the lithium film, which is not conducive to the performance of the battery cell. Similarly, the same problem is faced in the preparation of copper-lithium composite tapes, and it is impossible to accurately judge the content of lithium foil during the preparation process; Based on the above difficulties, the present invention provides a new strategy to simultaneously analyze the composition of the electrode sheet during the process of coating metallic lithium on the electrode sheet or foil, thereby realizing online monitoring of the electrode sheet and achieving quantitative lithium coating on the electrode sheet or foil. Summary of the invention
[0003] The technical problem to be solved by the present invention is that in the process of laminating metallic lithium on an electrode or foil, it is impossible to accurately determine the content of lithium foil in the preparation process. In view of the problems existing in the prior art, a method for preparing a composite electrode is provided.
[0004] The purpose and effect of the present invention are achieved by the following specific technical means: A method for preparing a composite electrode comprises the following steps: S1. Laminating metallic lithium on the negative electrode sheet or copper foil to prepare a composite electrode sheet; S2, performing component analysis on the composite electrode obtained in S1 to determine the metallic lithium content therein; S3. According to the analysis results of S2, the equipment parameters are adjusted to prepare a composite electrode with a lithium content within a preset range; S4. Prepare a lithium-ion battery using a positive electrode sheet, a separator, an electrolyte and the composite negative electrode sheet obtained in S3.
[0005] A further preferred embodiment: in step S1, the negative electrode sheet components include active materials, binders, and conductive agents, wherein the active materials include a combination of one or more of artificial graphite, natural graphite, soft carbon, hard carbon, silicon carbon, silicon oxygen, and lithium titanate.
[0006] A further preferred solution: in step S1, the copper foil includes one or more combinations of plain foil, microporous copper foil, and carbon-coated copper foil; The copper foil has a thickness of 3um-20um.
[0007] A further preferred solution: in step S1, the copper foil is coated with metallic lithium by one or more combinations of rolling, evaporation, and magnetron sputtering.
[0008] A further preferred embodiment: in step S1, the coated metallic lithium includes one or more combinations of lithium foil, lithium ribbon, lithium bar, lithium block, lithium foil with holes, lithium alloy, etc.; The thickness of metal lithium is 0.5um-100um.
[0009] In the step S2, the content of metallic lithium on the composite electrode is analyzed by using a laser induced breakdown spectrometer or an X-ray fluorescence spectrometer.
[0010] A further preferred solution: in step S2, the lithium content of the composite electrode metal lithium is 0.1%-90%; In step S3, if the lithium content in the analysis result exceeds or is lower than the preset standard, the equipment parameters such as temperature, electrode speed, pressure, etc. in S2 are corrected to adjust the metal lithium content of the electrode.
[0011] A further preferred embodiment: in step S4, the positive electrode material includes one or more combinations of lithium cobalt oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium vanadate, lithium manganate, lithium nickel oxide, lithium nickel cobalt manganese oxide, and lithium-rich manganese-based materials.
[0012] A further preferred embodiment: in step S4, the diaphragm is one of a PVDF coated diaphragm, a ceramic diaphragm, a PE base film, and a PP base film.
[0013] Beneficial effects of the present invention: The present invention introduces a sensor to monitor the metallic lithium content online, and can prepare a composite electrode with an accurate metallic lithium content. The battery cell made by the testing method has significantly improved cycle performance, with the cycle increased to 8500 times, and the storage performance is also significantly improved. The battery cell test data shows that the performance is stable, the lithium content is precisely controllable, and the battery cell performance is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] The present invention will be further described below in conjunction with the accompanying drawings.
[0015] Figure 1 This is a lithium plating process diagram of the negative electrode sheet of the present invention (calendering type); Figure 2 This is a process diagram of lithium plating of the negative electrode sheet of the present invention (evaporation type); Figure 3 This is an ICP test analysis table of four groups of battery cells according to an embodiment of the present invention; Figure 4 The following is a performance test table of the embodiments of the present invention and the comparative examples.
[0016] Figure 1-Figure 2 Middle: pole roll (1), composite pole piece roll (2), lithium metal layer (3), sensor (4), lithium plating equipment (5). DETAILED DESCRIPTION
[0017] In order to more clearly understand the above-mentioned objects, features and advantages of the present invention, Figure 1-4 The present invention is further described in detail with specific embodiments. The following embodiments are only examples for implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the scope of the present invention are all within the scope of patent protection of the present invention.
[0018] See also Figure 1-Figure 4 A method for preparing a composite electrode comprises the following steps: S1. Laminating metallic lithium on the negative electrode sheet or copper foil to prepare a composite electrode sheet; The negative electrode sheet components include active materials, binders, and conductive agents, wherein the active materials include one or more combinations of artificial graphite, natural graphite, soft carbon, hard carbon, silicon carbon, silicon oxygen, and lithium titanate; The copper foil includes one or more combinations of plain foil, microporous copper foil, and carbon-coated copper foil, and the thickness of the copper foil is 3um-20um; The method of coating copper foil with metallic lithium includes one or more combinations of rolling, evaporation, and magnetron sputtering; The coated metal lithium includes one or more combinations of lithium foil, lithium belt, lithium bar, lithium block, lithium foil with holes, lithium alloy, etc., and the thickness of the metal lithium is 0.5um-100um.
[0019] S2, performing component analysis on the composite electrode obtained in S1 to determine the metallic lithium content therein; The content of metallic lithium on the composite electrode is analyzed by using a laser induced breakdown spectrometer or an X-ray fluorescence spectrometer; The lithium content of the composite electrode metal lithium is 0.1%-90%.
[0020] S3. According to the analysis results of S2, the equipment parameters are adjusted to prepare a composite electrode with a lithium content within a preset range; If the lithium content in the analysis results exceeds or is lower than the preset standard, correct the temperature, electrode speed, pressure and other equipment parameters in S2 to adjust the metal lithium content of the electrode.
[0021] S4, preparing a lithium-ion battery using a positive electrode sheet, a separator, an electrolyte and the composite negative electrode sheet obtained in S3; The positive electrode material includes one or more combinations of lithium cobalt oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium vanadate, lithium manganate, lithium nickel oxide, lithium nickel cobalt manganate, and lithium-rich manganese-based materials; The diaphragm is one of PVDF coated diaphragm, ceramic diaphragm, PE base film, PP base film, and the lithium-ion battery includes hard-shell battery, soft-pack battery, cylindrical battery and other lithium-ion batteries; like Figure 1 As shown, the negative electrode sheet is in the shape of an electrode roll 1 in the initial state. When the negative electrode sheet is coated with metallic lithium, the negative electrode sheet is first unwound by a transmission device, and the negative electrode sheet passes through a lithium plating device 5. When the metallic lithium is evaporated, the lithium plating device 5 is preferably a crucible. The crucible evaporation causes the gaseous lithium ions to rise to the surface of the negative electrode sheet. In this way, double-layer lithium plating is performed to form a lithium metal layer 3 on both sides of the negative electrode sheet. The metallic lithium content is then monitored online through a sensor 4, and finally rolled up to form a composite electrode roll 2.
[0022] like Figure 2 As shown, the negative electrode sheet is in the shape of an electrode roll 1 in the initial state. When the negative electrode sheet is coated with metallic lithium, the negative electrode sheet is first unwound by a transmission device, and the negative electrode sheet passes through a lithium plating device 5. When the metallic lithium is rolled, metallic lithium extrusion equipment is arranged on the upper and lower sides of the negative electrode sheet, and the metallic lithium is squeezed on the upper and lower sides of the negative electrode sheet, and then rolled by the roller lithium plating device 5 to form a lithium metal layer 3. At the same time, the metallic lithium content is monitored online by a sensor 4, and finally rolled up to form a composite electrode roll 2.
[0023] Example 1, preparation of negative electrode sheet: using 6um copper foil as base foil, coating negative electrode slurry with a certain surface density on both sides of the foil, the negative electrode slurry composition ratio is graphite: binder: dispersant: conductive agent, which is 95%: 3%: 0.5%: 1.5% respectively, and then drying and rolling to make negative electrode sheet 1; Example 2: A composite electrode with a preset lithium content of 1.5% is prepared on the negative electrode 1 of Example 1 by using a calendering process, and is named electrode 2; Example 3, a composite electrode with a preset lithium content of 0.9% is prepared on the negative electrode 1 of Example 1 by using an evaporation process, and is named electrode 3; Example 4, a composite electrode with a preset lithium content of 50% is prepared by rolling on a copper foil, and is named electrode 4; Example 5, preparation of battery cells: Use lithium iron phosphate as the positive electrode material to prepare positive electrode sheets, which are matched with electrode sheet 1, electrode sheet 2, electrode sheet 3, and electrode sheet 4 respectively, and then prepare wound 3.5Ah soft-pack batteries, which are recorded as battery cell 1, battery cell 2, battery cell 3, and battery cell 4.
[0024] The ICP test was performed on the above-mentioned pole pieces 1, 2, 3 and 4 to analyze the metal lithium content. The results are shown in Table 1. The results show that the lithium content of the ICP test results is almost consistent with the preset value, indicating that the device can use sensor 4 to realize online monitoring of the lithium content of the pole piece, and the lithium coating equipment can be corrected according to the data of sensor 4, so that the pole piece can be accurately coated with lithium; The performance of battery cells 1, 2, 3 and 4 prepared in Example 5 was tested and analyzed. The results are shown in Table 2. After using the composite electrode described in this article, the first efficiency of battery cells 2, 3 and 4 was improved by 5.9%, 4.8% and 9.8% respectively compared with the reference group battery cell 1, which is a significant improvement. The internal resistance of several groups of batteries is almost the same as that of the non-pre-lithiation battery cell 1, and the cycle performance is significantly improved. The cycle of battery cell 2 is increased to 8500 times, and the storage performance is also significantly improved. The battery test data show that the composite electrode has stable performance, the lithium content is precisely controllable, and the battery performance is significantly improved.
Claims
1. A method for preparing a composite pole piece, characterized in that: The following steps are involved: S1. Laminating metallic lithium on the negative electrode sheet or copper foil to prepare a composite electrode sheet; S2, performing component analysis on the composite electrode obtained in S1 to determine the metallic lithium content therein; S3. According to the analysis results of S2, the equipment parameters are adjusted to prepare a composite electrode with a lithium content within a preset range; S4. Prepare a lithium-ion battery using a positive electrode sheet, a separator, an electrolyte and the composite negative electrode sheet obtained in S3.
2. The method for preparing a composite electrode according to claim 1, characterized in that: In the step S1, the negative electrode sheet components include active materials, binders, and conductive agents, wherein the active materials include a combination of one or more of artificial graphite, natural graphite, soft carbon, hard carbon, silicon carbon, silicon oxygen, and lithium titanate.
3. The method for preparing a composite electrode according to claim 1, characterized in that: In step S1, the copper foil includes one or more combinations of plain copper foil, microporous copper foil, and carbon-coated copper foil; The copper foil has a thickness of 3um-20um.
4. The method for preparing a composite pole piece according to claim 1, characterized in that: In the step S1, the method of coating the copper foil with metallic lithium includes one or more combinations of rolling, evaporation, and magnetron sputtering.
5. The method for preparing a composite pole piece according to claim 1, characterized in that: In the step S1, the coated metallic lithium includes one or more combinations of lithium foil, lithium ribbon, lithium bar, lithium block, lithium foil with holes, lithium alloy, etc.; The thickness of metal lithium is 0.5um-100um.
6. The method for preparing a composite pole piece according to claim 1, characterized in that: In step S2, the lithium content of the composite electrode metal lithium is 0.1%-90%.
7. The method for preparing a composite pole piece according to claim 1, characterized in that: In step S4, the positive electrode material includes one or more combinations of lithium cobalt oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium vanadate, lithium manganate, lithium nickel oxide, lithium nickel cobalt manganese oxide, and lithium-rich manganese-based materials.
8. The method for preparing a composite pole piece according to claim 1, characterized in that: In the step S4, the diaphragm is one of a PVDF coated diaphragm, a ceramic diaphragm, a PE base film, and a PP base film.
Citation Information
Patent Citations
Knowledge decision method for lithium battery coating production
CN107958988A
Lithium battery positive electrode material production quality evaluation and process optimization method
CN116629658A
Positive electrode active material sintering process monitoring method and online feedback device
CN117007458A
Method for manufacturing lithium battery electrode from lithium battery electrode material
CN117253989A
Lithium supplement agent homogenization method, battery cell and secondary battery
CN117673507A